2013
DOI: 10.1164/rccm.201211-2073oc
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibits T Helper Cell Type 9 Differentiation during Allergic Lung Inflammation via Down-regulation of IL-17RB

Abstract: Rationale: HelperCD41 T cell subsets, includingIL-9-and IL-10-producing T helper cell type 9 (Th9) cells, exist under certain inflammatory conditions. Cyclooxygenase (COX)-1 and COX-2 play important roles in allergic lung inflammation and asthma. It is unknown whether COX-derived eicosanoids regulate Th9 cells during allergic lung inflammation. Objectives: To determine the role of COX metabolites in regulating Th9 cell differentiation and function during allergic lung inflammation., COX-2 2/2 , and wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…COX-2 is the inducible form of the cyclooxygenase enzyme, regulated by cytokines and mitogens, and is responsible for prostaglandin synthesis associated with inflammation (FitzGerald, 2003). Consistent with the reports that IL-8 and COX-2 play important roles in lung inflammation (Nocker et al, 1996;Li et al, 2013), in vivo studies have shown that isoprene oxidation products cause airflow limitation and sensory irritation in mice (Rohr et al, 2003). In humans, the role of IL-8 and COX-2 in lung inflammation can be associated with diseases such as chronic obstructive pulmonary disease and asthma (Nocker et al, 1996;Peng et al, 2008;Fong et al, 2000).…”
Section: Biological Implicationssupporting
confidence: 56%
“…COX-2 is the inducible form of the cyclooxygenase enzyme, regulated by cytokines and mitogens, and is responsible for prostaglandin synthesis associated with inflammation (FitzGerald, 2003). Consistent with the reports that IL-8 and COX-2 play important roles in lung inflammation (Nocker et al, 1996;Li et al, 2013), in vivo studies have shown that isoprene oxidation products cause airflow limitation and sensory irritation in mice (Rohr et al, 2003). In humans, the role of IL-8 and COX-2 in lung inflammation can be associated with diseases such as chronic obstructive pulmonary disease and asthma (Nocker et al, 1996;Peng et al, 2008;Fong et al, 2000).…”
Section: Biological Implicationssupporting
confidence: 56%
“…MAG-EPA reduces airway hyperresponsiveness and lung inflammation in OVA-sensitized animals (5). COX-2-derived PGD2 and PGE2 regulate Th9 cell differentiation by suppressing IL-17RB expression via a protein kinase A-dependent mechanism (6). COX-2-derived PGE (2) is a hallmark of allergic inflammation.…”
mentioning
confidence: 99%
“…Further, chimeric mice engrafted with BM cells from mice implanted with PGE 2 -releasing pellets for 3 days have reduced DC-initiated immune responses [26]. Links between prostanoids, of which PGE 2 is the most abundant, and asthma are well recognized [27] and mechanistically, cyclooxygenase inhibition increases allergic inflammation in murine models of asthma [28,29].…”
Section: Discussionmentioning
confidence: 99%